2005
DOI: 10.1080/00288233.2005.9513637
|View full text |Cite
|
Sign up to set email alerts
|

The yield and nutritive value of maize hybrids grown for silage

Abstract: The effect of hybrid and plant population on yield, metabolisable energy content and nitrogen percentage of forage maize were investigated in a trial which included seven maize (Z. mays L.) hybrids established at 75 000, 100 000, and 140 000 plants/ha. Biomass yield and its distribution among morphological components were measured in all plots, while metabolisable energy content and nitrogen percentage of each component were measured in the 100 000 plants/ha plots only. There were significant hybrid difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
27
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 15 publications
8
27
2
1
Order By: Relevance
“…On the whole, this is similar to that reported by other authors (Eghball, 2000;Binder et al, 2002;Eghball et al, 2004;Hermann and Taube, 2004;O'Neill et al, 2004;Powell et al, 2004;Warren et al, 2006), although lower than the N concentration reported by Nevens and Reheul (2003) and Eghball et al (2004), andMillner et al (2005) for the same crop grown with different organic amendments.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…On the whole, this is similar to that reported by other authors (Eghball, 2000;Binder et al, 2002;Eghball et al, 2004;Hermann and Taube, 2004;O'Neill et al, 2004;Powell et al, 2004;Warren et al, 2006), although lower than the N concentration reported by Nevens and Reheul (2003) and Eghball et al (2004), andMillner et al (2005) for the same crop grown with different organic amendments.…”
Section: Discussionsupporting
confidence: 91%
“…2) for the different treatments over the two years was higher than that reported by other authors (Cox and Cherney, 2001;Millner et al, 2005). In general, during the two year of evaluation the dry matter production was similar between the treatments fertilized.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…A similar CP concentration in forage yield to our results (6.7-8.7%) was reported by Millner et al (2005) in New Zealand and by Lauer et al (2001) in the USA for hybrids developed in different decades of the last century. Lauer et al (2001) concluded that CP concentration in maize forage had not changed significantly since 1930.…”
Section: Discussionsupporting
confidence: 77%
“…This can be explained by better performance of earlier hybrids in poor years or conditions, and superior performance by later-maturity hybrids in suitable conditions. Delayed sowing of late hybrids in poor years can also decrease the DM yield (Millner et al 2005). We used hybrids with different-maturity in our study, they were exposed to possible unfavourable conditions in more or less diverse development stages, causing inconsistent effect on maize yield.…”
Section: Discussionmentioning
confidence: 99%